Health Care Workers and Patients as Trojan Horses: a COVID19 ward outbreak. Issue 3 (September 2020) - Asad, H.; Johnston, C.; Blyth, I.; Holborow, A.; Bone, A.; Porter, L.; Tidswell, P.; Healy, B.
Summary: Background: Transmission in healthcare settings can result in significant infections in healthcare workers and patients. Understanding infection dynamics has important implications for methods employed in hospitals to prevent nosocomial transmission events. Methods: In this case series report we describe a cluster of COVID-19 (Coronavirus disease 2019) in a tertiary care university hospital, in the early phases of the epidemic, after hospital visiting had been stopped and when the UK lockdown was in place. Findings: A 48 year old patient developed COVID-19 31 days post-admission and four days after admission to a medical ward from ITU. Infection was likely acquired from an asymptomatic or minimally symptomatic healthcare worker (HCW). Subsequent investigation over a 14 day period revealed symptoms in 23 staff members and five linked cases in patients on the same ward. Nine of the 23 affected staff members provided care for and had direct exposure with the index case. Four staff reported caring for the index case without use of personal protective equipment. One was coughed on directly by the patient 24 hours prior to the onset of symptoms. Conclusion: SARS CoV2 infection can be introduced to a ward area by asymptomatic and minimally symptomatic healthcare workers. Staff members and patients can act as Trojan horses carrying infection into and around the hospital, setting up unexpected transmission events. Transmission of infection from pre-symptomatic, asymptomatic and minimally symptomatic individuals means that universal use of measures to prevent transmission is required for successful reduction of transmission events in the hospital setting.